Bending-resistant high-transmittance epoxy resin composition and preparation method and application thereof
By scientifically comparing the use of polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughener and polycarbonate components, the problem of insufficient bending resistance and transparency in flexible displays and wearable devices is solved, and the comprehensive performance of the material is improved.
Patent Information
- Application Number
- CN202411849922.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
Existing epoxy resin materials are limited by inherent defects such as high brittleness and low transparency in emerging applications such as flexible displays and wearable devices, making it difficult to meet the needs of bending resistance and high transparency.
The scientific ratio of components such as polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughener and polycarbonate is used to reduce internal stress and increase toughness through the silicon oxygen structure. The core-shell rubber toughener improves bending resistance, and polycarbonate improves transparency and optical properties.
While basically maintaining the existing mechanical properties, the bending resistance and transparency of the material are significantly improved, meeting the needs of application scenarios such as flexible displays and wearable devices.
Smart Images

Figure BDA0005190291780000031 
Figure BDA0005190291780000041 
Figure BDA0005190291780000042
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of epoxy resin materials, and specifically relates to a bending-resistant and highly permeable epoxy resin composition, and a preparation method and application thereof. Background Art
[0002] As a thermosetting polymer material, epoxy resin occupies an important position in modern industry. Its application range is wide, covering many fields such as electronics, aerospace, and automobiles. Especially in the electronics industry, with the rapid development of science and technology, electronic products are moving towards lighter, thinner, and more flexible, which puts higher requirements on the performance of epoxy resin. Although traditional epoxy resin materials have certain application value, their inherent defects such as high brittleness and low transparency have become bottlenecks that restrict their further expansion in emerging application fields such as flexible displays and wearable devices. Therefore, how to improve the bending resistance and transparency of epoxy resin has become an important topic in current materials science research.
[0003] In order to improve the bending resistance of epoxy resin, researchers have conducted a lot of exploration and practice. Among them, the introduction of flexible segments is a common and effective method. By introducing flexible segments such as long-chain alkyls and siloxanes into the molecular structure of epoxy resin, the flexibility of the material can be significantly increased, thereby improving its bending resistance. These flexible segments can deform when subjected to external forces, absorb and disperse stress, thereby avoiding material fracture due to stress concentration. However, it is worth noting that the introduction of flexible segments often sacrifices the mechanical properties of the material, such as tensile strength and hardness, to a certain extent.
[0004] In addition to introducing flexible segments, designing a low cross-linking density system is also an effective strategy to improve the bending resistance of epoxy resins. Cross-linking density refers to the number or density of cross-linking points in a material, which directly affects the rigidity and toughness of the material. Traditional epoxy resins usually have a high cross-linking density, which makes the material prone to brittle fracture when subjected to external forces. By reducing the cross-linking density, the material can be better deformed when subjected to external forces, thereby improving its bending resistance. However, reducing the cross-linking density may also lead to a decrease in the material's heat resistance, chemical stability and mechanical properties.
[0005] In addition, the use of thermoplastic epoxy resin is also a way to improve the material's bending resistance. Unlike traditional thermosetting epoxy resins, thermoplastic epoxy resins can soften and flow when heated, thus having better processability and plasticity. This property enables thermoplastic epoxy resins to better adapt to deformation when subjected to external forces, thereby improving their bending resistance. However, thermoplastic epoxy resins generally have low heat resistance and mechanical strength, and are prone to creep and stress relaxation during use, affecting the mechanical properties of the material.
[0006] Researchers have also conducted in-depth explorations on improving the transparency of epoxy resins. The improvement of transparency mainly depends on the optimization and modification of the internal structure of the material. Fine chemical modification is an effective method. By reducing the polar groups in the epoxy resin molecules, the scattering and absorption of light by the material can be reduced, thereby improving its transparency. The presence of polar groups will cause tiny polar regions to form inside the material, which will scatter light and reduce the transparency of the material. Therefore, reducing the number and distribution of polar groups through chemical modification can significantly improve the transparency of the material. However, fine chemical modification usually requires complex synthesis processes and expensive raw materials, which to a certain extent limits its promotion in practical applications.
[0007] Designing an amorphous structure is also an effective strategy to improve the transparency of epoxy resin. Amorphous structure refers to the lack of clear crystal arrangement and orientation inside the material. This structure can avoid the scattering and absorption of light by crystal defects, thereby improving the transparency of the material. By adjusting the molecular structure and synthesis conditions of epoxy resin, epoxy resin materials with amorphous structure can be prepared. However, epoxy resins with amorphous structures often have lower glass transition temperatures and poorer thermal stability.
[0008] Nanocomposite technology is another innovative method to improve the transparency of epoxy resin. Nanofillers have the characteristics of small size, large specific surface area and high surface energy, which enable nanofillers to form uniform dispersion and effective interfacial interaction in the epoxy resin matrix. By selecting suitable nanofillers and suitable composite processes, nanocomposite epoxy resin materials with high transparency can be prepared. The introduction of nanofillers can not only improve the transparency of the material, but also improve its mechanical properties, heat resistance and flame retardancy. However, nanocomposite technology also has certain limitations, such as the uniformity of nanofiller dispersion, interfacial interaction and cost, which need to be further studied and resolved.
[0009] In summary, improving the bending resistance and transparency of epoxy resin is an important direction of current material science research. The bending resistance of epoxy resin can be improved to a certain extent by introducing flexible segments, designing low cross-linking density systems, and using thermoplastic epoxy resins; and the transparency of epoxy resin can be effectively improved by fine chemical modification, designing amorphous structures, nanocomposites and other technical means. However, these methods often have certain limitations and challenges in practical applications, such as decreased mechanical properties, increased costs, and increased process complexity. Therefore, it is necessary to continue to explore new modification methods and technical means to achieve comprehensive improvement and optimization of epoxy resin performance. Summary of the invention
[0010] The present invention aims to overcome at least one defect in the prior art and provide a bending-resistant and highly permeable epoxy resin composition, which improves the bending resistance and transparency of the material without significantly reducing the mechanical properties of the material.
[0011] In order to solve the above technical problems, the following technical solutions are adopted:
[0012] In the first aspect, a bending-resistant and highly permeable epoxy resin composition is proposed. The composition comprises the following components by mass: 30 to 60 parts of polyether polyol phosphate-modified silicone epoxy resin, 8 to 15 parts of core-shell rubber toughening agent, 2 to 4 parts of polycarbonate, 1 to 3 parts of curing agent, 0.5 to 2 parts of coupling agent, and 0.01 to 0.05 parts of accelerator. The molecular weight of the polyether polyol phosphate-modified silicone epoxy resin is 8,000 to 12,000.
[0013] This scheme uses the scientific proportion and synergistic effect of the above components to make the bending-resistant and highly transparent epoxy resin composition show excellent bending resistance and transparency while basically maintaining the existing mechanical properties. Among them, the silicon-oxygen structure in the molecular chain of the polyether polyol phosphate modified silicone epoxy resin can both reduce the internal stress of the epoxy resin and increase the toughness of the epoxy resin. The polyether polyol phosphate can also have a good toughening effect on the silicone epoxy resin. The combined effect of the two makes the polyether polyol phosphate modified silicone epoxy resin have very good toughness. The rubber body of the core layer of the core-shell rubber toughening agent has a toughening effect on the epoxy resin, and the shell layer can protect the core body to keep its original shape, thereby improving the bending resistance of the composition. Polycarbonate has high toughness and good optical properties. Compared with ordinary epoxy resin, polycarbonate has good bending resistance and fatigue resistance. Blending with epoxy resin can improve its toughness and bending resistance. The polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate synergistically improve the bending resistance of the material. The lack of any one of the polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate will reduce the bending resistance of the material, and too much or too little polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate are not conducive to achieving bending resistance and high light transmittance at the same time. In addition, the silicon and phosphorus atoms in the molecular chain of the polyether polyol phosphate modified silicone epoxy resin increase the refractive index of the epoxy resin. After adding other components, the refractive index of the composition is close to that of reinforcing materials such as glass fiber cloth, and semi-cured sheets, laminates, etc. can be made. The resulting products have the colorless transparency required by optical materials and meet the use requirements of optical materials.
[0014] Preferably, the polyether polyol phosphate modified silicone epoxy resin is a product obtained by reacting silicone epoxy resin with polyether polyol phosphate and extending the chain, and the silicone epoxy resin is a product obtained by reacting diphenylsilanediol with bisphenol A type epoxy resin in the presence of an alkaline catalyst. In other words, the structural formula of the polyether polyol phosphate modified silicone epoxy resin is as follows:
[0015]
[0016] The polyether polyol phosphate modified silicone epoxy resin designed in this scheme is prepared by modifying bisphenol A epoxy resin with diphenylsilanediol to prepare silicone epoxy resin, and then modifying the silicone epoxy resin with polyether polyol phosphate to prepare polyether polyol phosphate modified silicone epoxy resin, and then extending the chain with a chain extender to extend the molecular chain of the polyether polyol phosphate modified silicone epoxy resin, increase the high molar refractive groups (benzene rings), silicon and phosphorus atoms on the molecular chain, so that the refractive index of the polyether polyol phosphate modified silicone epoxy resin is between 1.60 and 1.68, and the refractive index of the composition after adding other components is between 1.55 and 1.62, which is close to the refractive index (1.55 to 1.65) of the reinforcing material glass fiber cloth, so the obtained composition has the colorless transparency required by the optical material and meets the use requirements of the optical material.
[0017] More preferably, the preparation process of polyether polyol phosphate modified silicone epoxy resin comprises the following steps:
[0018] S1. After uniformly mixing diphenylsilanediol and bisphenol A epoxy resin, adding an alkaline catalyst, reacting at 70-80°C until the reaction is complete, to obtain an organosilicon epoxy resin; the chemical reaction formula is:
[0019]
[0020] S2. The polyether polyol phosphate is mixed with the silicone epoxy resin obtained in step S1, heated to 70-80° C. while stirring, and reacted at 70-80° C. for 0.8-1.2 hours to obtain a polyether polyol phosphate-modified silicone epoxy resin; the chemical reaction formula is:
[0021]
[0022] S3. After the polyether polyol phosphate-modified silicone epoxy resin obtained in step S2 is uniformly mixed with the chain extender, an alkali metal hydroxide is added, and the mixture is reacted at 100 to 120° C. for 0.5 to 1 hour to obtain a polyether polyol phosphate-modified silicone epoxy resin having a molecular weight of 8000 to 12000.
[0023] In step S1, the weight fraction of bisphenol A epoxy resin is preferably more than 2 times the weight fraction of diphenylsilanediol, and the molar ratio of bisphenol A epoxy resin to diphenylsilanediol is most preferably 3:1; the alkaline catalyst is preferably a NaOH aqueous solution, the concentration of the NaOH aqueous solution is preferably 20-30wt%, and the amount of NaOH in the NaOH aqueous solution is equivalent to 1.5 times the amount of hydroxyl group of diphenylsilanediol. In step S2, the mass ratio of polyether polyol phosphate to organosilicon epoxy resin is preferably 1:(8-12). In step S3, the molar ratio of polyether polyol phosphate modified organosilicon epoxy resin to chain extender is preferably (50-100):(30-50); the chain extender is selected from at least one of terephthalic acid, phthalic acid, dimethyl terephthalate, and dimethyl phthalate; the alkali metal hydroxide is selected from sodium hydroxide or potassium hydroxide, and the molar ratio of alkali metal to terephthalic acid is (0.01-0.05):1.
[0024] Preferably, the core-shell rubber toughening agent is selected from at least one of a resin whose core is polybutyl acrylate and whose shell is polymethyl methacrylate (referred to as PBA / PMMA core-shell resin), a resin whose core is cross-linked polybutadiene and whose shell is polymethyl methacrylate (referred to as cross-linked PB / PMMA core-shell resin), a resin whose core is silicone rubber and whose shell is polymethyl methacrylate (referred to as silicone rubber / PMMA core-shell resin), and a resin whose core is styrene-butadiene rubber and whose shell is polymethyl methacrylate (referred to as SBR / PMMA core-shell resin).
[0025] Preferably, the curing agent is selected from one of tetraethyl orthosilicate, triethanolamine, and a mixture of triethanolamine and dibenzoyl peroxide.
[0026] Preferably, the coupling agent is selected from at least one of vinyltrichlorosilane, vinyltriethoxysilane and γ-aminopropyltriethoxysilane.
[0027] Preferably, the accelerator is selected from at least one of N,N-dimethylbenzylamine, triethylamine, N,N-dimethylaniline, imidazole accelerators and peroxide accelerators.
[0028] The above-mentioned bending-resistant high-transmittance epoxy resin composition can be prepared by the following method: adding the dissolved curing agent, polyether polyol phosphate modified silicone epoxy resin and core-shell rubber toughening agent to polycarbonate completely dissolved in tetrahydrofuran, stirring for 0.4 to 0.6 hours, adding the coupling agent and the accelerator dropwise under stirring, and continuing to stir for 0.4 to 0.6 hours. The stirring speed is preferably 1500 to 2000 rpm.
[0029] In a second aspect, a prepreg is provided, which comprises a reinforcing material and a resin attached to the reinforcing material, wherein the resin is made of the above-mentioned bending-resistant and high-permeability epoxy resin composition.
[0030] The bend-resistant and highly transparent epoxy resin composition used in the semi-cured sheet is coordinated with an appropriate amount of polyether polyol phosphate-modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate, so that the bend-resistant and highly transparent epoxy resin composition exhibits excellent bending resistance and transparency while basically maintaining the existing mechanical properties, providing an ideal material choice for application scenarios such as flexible displays and wearable devices that require bend resistance and high transparency.
[0031] The reinforcing material may be glass fiber cloth having a refractive index close to that of the bending-resistant high-transmittance epoxy resin composition, such as 2116 cloth, to achieve a high-transmittance effect.
[0032] The prepreg sheet can be prepared by the following method: impregnating the reinforcing material with the bending-resistant high-permeability epoxy resin composition and baking at 160-180° C. for 1-3 minutes.
[0033] In a fourth aspect, a laminate is provided, which comprises at least one prepreg sheet.
[0034] The semi-cured sheet used in this laminate has excellent bending resistance and transparency. The laminate produced therefrom can be used in scenes such as flexible displays and wearable devices that require bending resistance and high transparency.
[0035] The laminate can be prepared by the following method: stacking the prepreg and other prepregs, or a plurality of prepregs, to form a laminate, covering the upper and lower surfaces of the laminate with a smooth release film, placing the laminate in a vacuum press with programmable temperature and pressure control, and pressing the laminate under vacuum at 10 to 15 kgf / cm 2 Under the pressure condition, the product temperature is cured at 160-180℃ for 90 minutes.
[0036] Compared with the prior art, this scheme has the following beneficial effects: Through the scientific proportion and synergistic effect of the above-mentioned components, this scheme makes the bending-resistant and high-transmittance epoxy resin composition show excellent bending resistance and transparency while basically maintaining the existing mechanical properties. Among them, the silicon-oxygen structure in the molecular chain of polyether polyol phosphate modified silicone epoxy resin can both reduce the internal stress of epoxy resin and increase the toughness of epoxy resin, and polyether polyol phosphate can also play a good toughening effect on silicone epoxy resin. Under the joint action of the two, the polyether polyol phosphate modified silicone epoxy resin has very good toughness. The rubber body of the core layer of the core-shell rubber toughening agent has a toughening effect on epoxy resin, and the shell layer can protect the core body to keep its original shape, thereby improving the bending resistance of the composition. Polycarbonate has high toughness and good optical properties. Compared with ordinary epoxy resin, polycarbonate has good bending resistance and fatigue resistance. Blending with epoxy resin can improve its toughness and bending resistance. The polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate synergistically improve the bending resistance of the material. The lack of any one of the polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate will reduce the bending resistance of the material, and too much or too little polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate are not conducive to achieving bending resistance and high light transmittance at the same time. In addition, the silicon and phosphorus atoms in the molecular chain of the polyether polyol phosphate modified silicone epoxy resin increase the refractive index of the epoxy resin. After adding other components, the refractive index of the composition is close to that of reinforcing materials such as glass fiber cloth, and semi-cured sheets, laminates, etc. can be made. The resulting products have the colorless transparency required by optical materials and meet the use requirements of optical materials. DETAILED DESCRIPTION
[0037] This proposal proposes a bending-resistant high-transmittance epoxy resin composition and its preparation method and application. The bending-resistant high-transmittance epoxy resin composition includes the following components by mass: 30-60 parts of polyether polyol phosphate modified silicone epoxy resin, 8-15 parts of core-shell rubber toughening agent, 2-4 parts of polycarbonate, 1-3 parts of curing agent, 0.5-2 parts of coupling agent, and 0.01-0.05 parts of accelerator.
[0038] The molecular weight of polyether polyol phosphate modified silicone epoxy resin is 8000-12000. It is the product obtained by the reaction and chain extension of silicone epoxy resin and polyether polyol phosphate. Silicone epoxy resin is the product obtained by the reaction of diphenylsilanediol and bisphenol A epoxy resin in the presence of an alkaline catalyst. The structural formula of polyether polyol phosphate modified silicone epoxy resin is:
[0039]
[0040] The core-shell rubber toughening agent is preferably at least one of a resin having a core of polybutyl acrylate and a shell of polymethyl methacrylate (referred to as PBA / PMMA core-shell resin), a resin having a core of cross-linked polybutadiene and a shell of polymethyl methacrylate (referred to as cross-linked PB / PMMA core-shell resin), a resin having a core of silicone rubber and a shell of polymethyl methacrylate (referred to as silicone rubber / PMMA core-shell resin), and a resin having a core of styrene-butadiene rubber and a shell of polymethyl methacrylate (referred to as SBR / PMMA core-shell resin).
[0041] The curing agent is preferably one of tetraethyl orthosilicate, triethanolamine, and a mixture of triethanolamine and dibenzoyl peroxide.
[0042] The coupling agent is preferably at least one of vinyltrichlorosilane, vinyltriethoxysilane and γ-aminopropyltriethoxysilane.
[0043] The accelerator is preferably at least one of N,N-dimethylbenzylamine, triethylamine, N,N-dimethylaniline, imidazole accelerators and peroxide accelerators.
[0044] The bending-resistant and highly permeable epoxy resin composition can be prepared by the following method: adding the dissolved curing agent, polyether polyol phosphate-modified silicone epoxy resin and core-shell rubber toughening agent to the polycarbonate completely dissolved in tetrahydrofuran, stirring at a high speed of 1500 to 2000 rpm for 0.4 to 0.6 hours, adding the coupling agent and the accelerator dropwise under stirring, and continuing the high-speed stirring for 0.4 to 0.6 hours.
[0045] The bending-resistant high-permeability epoxy resin composition can be used to make a prepreg. The prepreg includes a reinforcing material and a resin attached to the reinforcing material, and the resin is made of the bending-resistant high-permeability epoxy resin composition. The prepreg can be prepared by the following method: impregnating the reinforcing material with the bending-resistant high-permeability epoxy resin composition and baking at 160-180°C for 1-3 minutes.
[0046] Prepregs can be used to make laminates. Laminates can be prepared by the following method: stack the above-mentioned prepregs with other prepregs, or stack a plurality of the above-mentioned prepregs to form a laminate, cover the upper and lower surfaces of the laminate with a smooth release film, place the laminate in a programmable temperature and pressure controlled vacuum press, and press the laminate in a vacuum state at 10-15 kgf / cm 2 Under the pressure condition, the product temperature is cured at 160-180℃ for 90 minutes.
[0047] In order to allow those skilled in the art to better understand this solution, the solution is further described in detail below in conjunction with specific examples. The process methods used in the examples are all conventional methods unless otherwise specified; the materials used are all commercially available unless otherwise specified.
[0048] Polyether polyol phosphate modified silicone epoxy resin: homemade. The preparation process is: after the mass ratio of 1:3 diphenylsilane diol and bisphenol A epoxy resin are mixed evenly, a 25wt% NaOH aqueous solution is added, the molar ratio of NaOH to diphenylsilane diol is 3:1, and the reaction is carried out at 80°C until the reaction is complete to obtain a silicone epoxy resin. Mix polyether polyol phosphate with a mass ratio of 1:10 and silicone epoxy resin, heat to 80°C while stirring, and react at 80°C for 1 hour to obtain polyether polyol phosphate modified silicone epoxy resin. After the molar ratio of 75:40 polyether polyol phosphate modified silicone epoxy resin and terephthalic acid alcohol are mixed evenly, sodium hydroxide is added, the molar ratio of sodium hydroxide to terephthalic acid alcohol is 0.03:1, and the reaction is carried out at 110°C for 1 hour to obtain a polyether polyol phosphate modified silicone epoxy resin with a molecular weight of 8000 to 12000.
[0049] SBR / PMMA core-shell resin: Japan Kane Ace MX-125, PBA / PMMA core-shell resin: Japan Kane Ace M-577, cross-linked PB / PMMA core-shell resin: Japan Kane Ace MX-153, silicone rubber / PMMA core-shell resin: Japan Kane Ace MX-962.
[0050] Polycarbonate: Covestro PC.
[0051] Ethyl orthosilicate: Shanghai Experimental Reagent Co., Ltd., triethanolamine: Shandong Yuquan New Material Technology Co., Ltd., dibenzoyl peroxide: Jinan Yucai Chemical Co., Ltd.
[0052] Vinyltrichlorosilane: Shanghai Yien Chemical Technology Co., Ltd., Vinyltriethoxysilane: Shanghai Yien Chemical Technology Co., Ltd., γ-aminopropyltriethoxysilane: Chinese Academy of Sciences KH550.
[0053] N,N-Dimethylbenzylamine: Tai'an Jiangzhou Biotechnology Co., Ltd., triethylamine: Jiangsu Runfeng Synthetic Technology Co., Ltd., N,N-dimethylaniline: Changde Changlian Chemical Co., Ltd., 2-methylimidazole: Guangzhou Deshui Chemical Co., Ltd.
[0054] Example 1
[0055] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 30 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0056] Example 2
[0057] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 40 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0058] Example 3
[0059] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0060] Example 4
[0061] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 50 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0062] Example 5
[0063] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 60 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0064] Example 6
[0065] In terms of mass fractions, 4 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 30 parts of polyether polyol phosphate modified silicone epoxy resin, and 15 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0066] Example 7
[0067] In terms of mass fractions, 4 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 60 parts of polyether polyol phosphate modified silicone epoxy resin, and 15 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0068] Example 8
[0069] In terms of mass fractions, 2 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 1 part of the dissolved triethanolamine, 30 parts of polyether polyol phosphate modified silicone epoxy resin, and 8 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 0.5 parts of KH550 and 0.01 parts of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0070] Example 9
[0071] In terms of mass fractions, 2 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 1 part of the dissolved triethanolamine, 60 parts of polyether polyol phosphate modified silicone epoxy resin, and 8 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 0.5 parts of KH550 and 0.01 parts of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0072] Example 10
[0073] In terms of mass fractions, 4 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 15 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0074] Embodiment 11
[0075] In terms of mass fractions, 2 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 1 part of the dissolved triethanolamine, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 8 parts of SBR / PMMA core-shell resin were added to the mixing bottle. After stirring at 1800rpm for 0.5 hours, 0.5 parts of KH550 and 0.01 parts of 2-methylimidazole were added dropwise under stirring. After high-speed dispersion at 1800rpm for 0.5 hours, a glue solution was prepared. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0076] Example 12
[0077] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800 rpm for 2 to 4 hours. After confirming that the polycarbonate was completely dissolved, 3 parts of dissolved tetraethyl orthosilicate, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of cross-linked PB / PMMA core-shell resin were added to the mixing bottle. After stirring at 1800 rpm for 0.5 hours, 2 parts of vinyl triethoxysilane and 0.05 parts of N, N-dimethylbenzylamine were added dropwise under stirring. After high-speed dispersion at 1800 rpm for 0.5 hours, a glue solution was prepared. This glue solution was used to impregnate 2116 cloth (basic weight 105 g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0078] Example 13
[0079] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800 rpm for 2 to 4 hours. After confirming that the polycarbonate was completely dissolved, 3 parts of dissolved tetraethyl orthosilicate, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of silicone rubber / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800 rpm for 0.5 hours. Then, 2 parts of vinyl trichlorosilane and 0.05 parts of triethylamine were added dropwise under stirring, and dispersed at 1800 rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105 g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0080] Embodiment 14
[0081] In terms of mass, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 1 part of dissolved triethanolamine, 2 parts of dissolved dibenzoyl peroxide, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of PBA / PMMA core-shell resin were added to the mixing bottle. After stirring at 1800rpm for 0.5h, 2 parts of vinyl triethoxysilane and 0.05 parts of N,N-dimethylaniline were added dropwise under stirring. After high-speed dispersion at 1800rpm for 0.5h, a glue solution was prepared. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0082] Comparative Example 1
[0083] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 45 parts of silicone-modified epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0084] Comparative Example 2
[0085] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine and 55 parts of polyether polyol phosphate modified silicone epoxy resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare the glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0086] Comparative Example 3
[0087] In terms of mass fractions, 2 parts of dissolved triethanolamine, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 13 parts of SBR / PMMA core-shell resin were added to the mixing bottle, stirred at 1800 rpm for 0.5 h, and then 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800 rpm for 0.5 h to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105 g / m 2), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0088] Comparative Example 4
[0089] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 20 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0090] Comparative Example 5
[0091] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 70 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0092] Comparative Example 6
[0093] In terms of mass fractions, 3 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 20 parts of SBR / PMMA core-shell resin were added to the mixing bottle, and stirred at 1800rpm for 0.5 hours. Then, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring, and dispersed at 1800rpm for 0.5 hours to prepare a glue solution. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0094] Comparative Example 7
[0095] In terms of mass, 8 parts of polycarbonate and 30 parts of tetrahydrofuran were added to the mixing bottle, and stirred at 1800rpm for 2-4 hours. After confirming that the polycarbonate was completely dissolved, 2 parts of dissolved triethanolamine, 45 parts of polyether polyol phosphate modified silicone epoxy resin, and 10 parts of SBR / PMMA core-shell resin were added to the mixing bottle. After stirring at 1800rpm for 0.5 hours, 1 part of KH550 and 0.01 part of 2-methylimidazole were added dropwise under stirring. After high-speed dispersion at 1800rpm for 0.5 hours, a glue solution was prepared. This glue solution was used to impregnate 2116 cloth (basic weight 105g / m 2 ), and baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped to form a laminate, and a smooth release film was covered on each of the upper and lower surfaces of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure condition, the product temperature was cured at 170°C for 90 minutes to produce a laminate with a thickness of 0.2 mm.
[0096] The performance tests were conducted on the laminates obtained from the above-mentioned embodiments and comparative examples respectively. The test items include: elastic modulus test, transmittance test and bending resistance test. Elastic modulus test: Test in accordance with IPC-TM-650 2.4.22.1. Transmittance test: Set the wavelength of the spectrophotometer to 254nm, set the transmittance of pure water to 100%, and test and read the transmittance of each laminate sample in turn. Bending resistance test: Use a YUASA bending resistance machine to test, prepare a sample with a width of 2.5cm and a length of 6cm, fix the sample, set the speed to 30r / min, set the number of bending times to 100,000 times, start the test, and observe whether the sample has peeling, breakage, whitening, etc. after the test. The test results are shown in Tables 1 to 2.
[0097] Table 1 Ingredients, dosages and test results of Examples 1 to 12
[0098]
[0099]
[0100]
[0101] Table 2 Ingredients, dosages and test results of comparative examples 1 to 7
[0102]
[0103] As shown in Tables 1 and 2, the laminates prepared from the bending-resistant high-transmittance epoxy resin composition of this embodiment not only maintain the existing mechanical performance level, but also have excellent light transmittance and bending resistance. Specifically, the light transmittance of the laminates prepared in all embodiments exceeds 90%, and they can pass the 100,000-time bending test.
[0104] Compared with Example 3, in Comparative Example 1, the polyether polyol phosphate modified silicone epoxy resin is replaced by silicone modified epoxy resin in equal amounts, and the light transmittance and bending resistance are greatly reduced; in Comparative Example 2, the core-shell rubber toughening agent (SBR / PMMA core-shell resin) is replaced by polyether polyol phosphate modified silicone epoxy resin in equal amounts, and the bending resistance is significantly reduced; in Comparative Example 3, the polycarbonate is replaced by core-shell rubber toughening agent (SBR / PMMA core-shell resin) in equal amounts, and the bending resistance is significantly reduced. It can be seen that the lack of any one of polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent, and polycarbonate will reduce the bending resistance of the laminate, and the lack of polyether polyol phosphate modified silicone epoxy resin will also reduce the light transmittance of the laminate.
[0105] Compared with Example 3, Comparative Example 4 added less than the specified amount of polyether polyol phosphate modified silicone epoxy resin, and the light transmittance decreased significantly; Comparative Example 5 added more than the specified amount of polyether polyol phosphate modified silicone epoxy resin, and the bending resistance decreased significantly; Comparative Example 6 added more than the specified amount of core-shell rubber toughening agent (SBR / PMMA core-shell resin), and the light transmittance decreased significantly; Comparative Example 7 added more than the specified amount of polycarbonate, and the bending performance decreased significantly. It can be seen that too much or too little polyether polyol phosphate modified silicone epoxy resin, core-shell rubber toughening agent and polycarbonate are not conducive to achieving both bending resistance and high light transmittance.
[0106] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all implementation methods here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A bending-resistant high-permeability epoxy resin composition, characterized in that: The composition, in parts by mass, comprises the following components: 30-60 parts of polyether polyol phosphate modified silicone epoxy resin, 8-15 parts of core-shell rubber toughening agent, Polycarbonate 2-4 parts, 1-3 parts of curing agent, 0.5-2 parts of coupling agent, and Accelerator 0.01-0.05 parts; Wherein, the molecular weight of the polyether polyol phosphate modified silicone epoxy resin is 8000-12000.
2. The bending-resistant high-permeability epoxy resin composition according to claim 1, characterized in that: The structural formula of the polyether polyol phosphate modified silicone epoxy resin is:
3. The bending-resistant high-permeability epoxy resin composition according to claim 1, characterized in that: The polyether polyol phosphate modified silicone epoxy resin is a product obtained by reacting silicone epoxy resin with polyether polyol phosphate and extending the chain. The silicone epoxy resin is a product obtained by reacting diphenylsilanediol with bisphenol A epoxy resin in the presence of an alkaline catalyst.
4. The bending-resistant high-permeability epoxy resin composition according to claim 3, characterized in that: The preparation process of the polyether polyol phosphate modified silicone epoxy resin comprises the following steps: S1. After uniformly mixing diphenylsilanediol and bisphenol A epoxy resin, adding a basic catalyst, reacting at 70 to 80° C. until the reaction is complete, to obtain a silicone epoxy resin; S2. The polyether polyol phosphate is mixed with the silicone epoxy resin obtained in step S1, heated to 70 to 80° C. while stirring, and reacted at 70 to 80° C. for 0.8 to 1.2 hours to obtain a polyether polyol phosphate-modified silicone epoxy resin; S3. After the polyether polyol phosphate-modified silicone epoxy resin obtained in step S2 is uniformly mixed with the chain extender, an alkali metal hydroxide is added, and the mixture is reacted at 100 to 120° C. for 0.5 to 1 hour to obtain a polyether polyol phosphate-modified silicone epoxy resin having a molecular weight of 8000 to 12000.
5. The bending-resistant high-permeability epoxy resin composition according to claim 4, characterized in that: In step S1, the weight of the bisphenol A epoxy resin is more than twice the weight of diphenylsilanediol; the alkaline catalyst is a NaOH aqueous solution, the concentration of the NaOH aqueous solution is 20-30wt%, and the amount of NaOH in the NaOH aqueous solution is equivalent to 1.5 times the amount of hydroxyl groups of diphenylsilanediol; In step S2, the mass ratio of the polyether polyol phosphate to the silicone epoxy resin is 1:(8-12); In step S3, the molar ratio of the polyether polyol phosphate modified silicone epoxy resin to the chain extender is (50-100):(30-50); the chain extender is selected from at least one of terephthalic acid, phthalic acid, dimethyl terephthalate, and dimethyl phthalate; the alkali metal hydroxide is selected from sodium hydroxide or potassium hydroxide, and the molar ratio of the alkali metal in the alkali metal hydroxide to terephthalic acid is (0.01-0.05):
1.
6. The bending-resistant high-permeability epoxy resin composition according to any one of claims 1 to 5, characterized in that: The core-shell rubber toughening agent is selected from at least one of a resin having a core of polybutyl acrylate and a shell of polymethyl methacrylate, a resin having a core of cross-linked polybutadiene and a shell of polymethyl methacrylate, a resin having a core of silicone rubber and a shell of polymethyl methacrylate, and a resin having a core of styrene-butadiene rubber and a shell of polymethyl methacrylate.
7. The bending-resistant high-permeability epoxy resin composition according to any one of claims 1 to 5, characterized in that: The curing agent is selected from one of tetraethyl orthosilicate, triethanolamine, and a mixture of triethanolamine and dibenzoyl peroxide; and / or The coupling agent is selected from at least one of vinyl trichlorosilane, vinyl triethoxysilane and γ-aminopropyl triethoxysilane; and / or The accelerator is selected from at least one of N,N-dimethylbenzylamine, triethylamine, N,N-dimethylaniline, imidazole accelerators and peroxide accelerators.
8. A method for preparing the bending-resistant high-permeability epoxy resin composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding a dissolved curing agent, a polyether polyol phosphate modified silicone epoxy resin and a core-shell rubber toughening agent to polycarbonate completely dissolved in tetrahydrofuran, stirring for 0.4 to 0.6 hours, adding a coupling agent and an accelerator dropwise under stirring, and continuing stirring for 0.4 to 0.6 hours.
9. A prepreg, characterized in that: The prepreg comprises a reinforcing material and a resin attached to the reinforcing material, wherein the resin is made of the bending-resistant and high-permeability epoxy resin composition according to any one of claims 1 to 8.
10. A laminated board, characterized in that: The laminate comprises at least one prepreg according to claim 9.